Unusually low infection rate of Dirofilaria immitis in its wildlife hosts by the northern border of the Mediterranean climate zone in Hungary - Nagy, Eszter; Nagy, Rebeka Ráhel; Csivincsik, Ágnes; Halász, Tibor; Moloi, Sibusiso; Kovács, Melinda; Nagy, Gábor; Tari, Tamás (Frontiers in Veterinary Science, 2025)
Wildlife-originating zoonotic pathogens represent a special form of human-wildlife conflict. Disease spillover and spillback can cause health damage to both sides. Canine heartworm (Dirofilaria immitis) is considered a climate-sensitive parasite due to the special environmental demands of its mosquito vectors. Abundant wild mesocarnivores in Europe, the golden jackal (Canis aureus), the red fox (Vulpes vulpes), and Eurasian badger (Meles meles) are frequently accused of being a natural reservoir for the parasite. This study investigated the heartworm infection rate in the populations of jackals (N = 305), foxes (N = 361) and badgers (N = 29) by the northern border of the Mediterranean climate zone and, despite the suitable climatic conditions, found unusually low prevalence in these hosts (2.3% in jackals, 1.4% in foxes, 0% in badgers). Analysis of the spatial distribution of infection confirmed that temperature and local socioeconomic development influenced the disease occurrence significantly. Precipitation and land use did not show any impact on the epidemiology of canine heartworm in wild caniforms. These results suggested that wild carnivores are sentinels of D. immitis spilled over from the domestic cycle rather than vice versa.